The early chronology of long vowels in Balto-Slavic - Kortlandt, Frederik (Baltistica, 2012)
The attractiveness of projecting a variety of formations back in time lies in the freedom it allows the investigator to choose between different reconstructions in accordance with his theoretical preconceptions. The history of Indo-European reconstruction can to a large extent be seen as a gradual limitation of this freedom. It is therefore advisable to be cautious when a new theory enlarges rather than restricts the number of possible reconstructions.
Keywords: Balto-Slavic; long vowels; historical phonology; chronology